PENERAPAN STRATEGI GAME BASED LEARNING DALAM PEMBELAJARAN IPAS PADA SISWA ADHD KELAS III SDN I PAGAR AIR KABUPATEN ACEH BESAR - Rizqa Ramadhani; Mislinawati; Tursinawati (STKIP Subang, 2026)
Learning of IPAS in elementary schools still presents challenges for students with Attention Deficit Hyperactivity Disorder (ADHD), particularly in maintaining attention, controlling hyperactive and impulsive behaviors, and achieving active learning engagement. These conditions require the implementation of adaptive learning strategies that align with the characteristics of students with ADHD. This study aims to describe the implementation of the Game Based Learning (GBL) strategy in IPAS learning on the topic of animal body parts and their functions for third-grade students with ADHD at SD Negeri 1 Pagar Air, Aceh Besar Regency. This study employed a qualitative approach with a descriptive research design. The research subjects consisted of a third-grade teacher and 28 third-grade students, five of whom were identified as having ADHD. Data were collected through observations and interviews using teacher and ADHD student observation sheets as well as a teacher interview guide. Data analysis was conducted using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through technique triangulation. The results indicate that the implementation of the Game Based Learning strategy supports the achievement of IPAS learning objectives, increases active participation and learning motivation of students with ADHD, and gradually assists in managing their learning behaviors, although some ADHD symptoms still appeared during the learning process. Learning activities were also able to channel students’ energy in a positive and directed manner, with the Battle Ship game being the most effective in helping students maintain focus. Therefore, the Game Based Learning strategy is recommended as an effective IPAS learning strategy for students with ADHD in elementary schools, provided that optimal time management and teacher guidance are ensured.